Neoliberalismo e desigualdade social: reflexos na distribuição de renda da Argentina de 1989 a 2001 - SILVA, Laryssa Costa (2020)
Argentina began the 21st century with a deep political and economic crisis, the social consequences of which were devastating. The State reached extreme indebtedness, neglecting the most basic needs of the population, resulting in widespread questioning regarding the neoliberal-based structural reforms imposed by the International Monetary Fund. This work aims to investigate and evaluate how these reforms adopted by Argentina, in the period from 1989 to 2001, influenced the scope of social inequality. The collapse of the 2001 crisis and the socioeconomic difficulties experienced by Argentina showed the exhaustion of neoliberal policies. Through official documents, we highlight the role played by international financial institutions in propagating neoliberal economic policies admitted in Argentina until the explosion of the social crisis and during its development. Financial expansion, opening of the commercial market, privatizations of state-owned companies, labor and social security reforms, and austerity policy were the main actions on the neoliberal agenda. Therefore we conclude that the consequences of neoliberal political reforms resulted in: an insufficient demand that did not support long-term growth, an economy more vulnerable to speculative attacks and a high concentration of income, followed by the increase in poverty and indigence, unemployment and the destruction of workers' ability to articulate. It is possible to affirm that the increase in social inequality in Argentina during this period was the result of the government's dedication to implementing the economic policies promoted by the IMF, which serve the interests of the ruling class.